Antibacterial and antibiofilm activity of microencapsulated and non-microencapsulated Syzygium aromaticum essential oil (Research, Society and Development, 2022)
The aim of this work was to evaluate the antibacterial and antibiofilm activity of microencapsulated and non-microencapsulated clove (Syzygium aromaticum) essential oil on multidrug-resistant Staphylococcus aureus strains. Antibacterial activity was performed by disk diffusion and broth microdilution techniques to determine the Minimum Inhibitory Concentration (MIC) and Minimum Bactericidal Concentration (MBC) of the essential oil. For the antibiofilm activity, strains of S. aureus that were sensitive to the action of the essential oil were used. Five isolates were sensitive to the action of the essential oil by the disk diffusion test whose MIC was 10 μL.mL-1 and the CBM was 20 μL.mL-1. Of these five, four were able to form biofilms with adhesion greater than 107 CFU.cm-2. The microencapsulated oil showed a better antibiofilm effect with a reduction of about 2 log CFU.cm-2 in the multiresistant S. aureus analyzed, and the non-microencapsulated oil reduced approximately 1.1 log CFU.cm-2 showing the high efficiency of the oil with microencapsulation. The use of microencapsulated Syzygium aromaticum essential oil could serve as a promising alternative in the control of multiresistant and biofilm forming bacteria on stainless steel surfaces, presenting some advantages compared to the one used in its original form, mainly with regard to transport, content preservation, handling and use in food matrices.